The influence of orientalists on the Quranists in the issue of writing down the Sunnah - presentation and criticism - Abdulwahab Ghafor Kareem; Luqman Samad Khudhur (Zanco Journal of Humanity Sciences)
This study deals with a very important issue, which is the issue of transcribing the Sunnah as well as the study focused on the position of the Orientalists and the Qur’anic movement in this regard, and the extent to which the Qur’anists were affected by the opinions and sayings of Orientalists about the collecting and writing down of the Prophetic Sunnah. In addition, it explains the reasons for the delay in transcribing the Sunnah and its consequences for them. The opinions of the Orientalists differed on this issue, but they generally agreed that the writing of the Sunnah of the Prophet was delayed, until after the first century or until after the middle of the second century, as the majority of the Qur’anists agreed with them and repeated their opinions on this issue without referring to the competent sources to realize the truth in this regard and its implications, problems, and knowledge of its reality, they are influenced by opinions of orientalists in this matter. The orientalists and the Quranists have based this issue and made it a wide gate to criticize the authenticity of the Sunnah and its position in Islamic legislation as well as they questioned its credibility and the honesty of its narrations.